2018
DOI: 10.1002/tox.22571
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress‐mediated autophagic cell death participates in the neurotoxic effect on SH‐SY5Y cells induced by excessive iodide

Abstract: Excessive iodide could induce intellectual damage in children, which has attracted broad attention. To investigate the neurotoxic effect of iodide and its mechanism, a human dopaminergic neuroblastoma cell line (SH-SY5Y) was treated with different concentrations of potassium iodide (KI). The results showed that excessive iodide could decrease cell viability, reduce glutathione (GSH) and superoxide dismutase (SOD), and increase the degree of autophagy (by changing the cellular ultrastructure and raising the aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Existing findings have indicated that molecular iodine (I 2 ) treatment enhanced the features of autophagy in human breast cancer cell line (MDA‐MB231) . Simultaneously, our study has shown that exposure to potassium iodide could cause autophagic cell death mediated by oxidative stress in SH‐SY5Y cells . In this regard, oxidative stress and autophagy may play a prominent role in the damage action mechanism of excessive iodine.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…Existing findings have indicated that molecular iodine (I 2 ) treatment enhanced the features of autophagy in human breast cancer cell line (MDA‐MB231) . Simultaneously, our study has shown that exposure to potassium iodide could cause autophagic cell death mediated by oxidative stress in SH‐SY5Y cells . In this regard, oxidative stress and autophagy may play a prominent role in the damage action mechanism of excessive iodine.…”
Section: Introductionsupporting
confidence: 51%
“…Conversely, as autophagy is often induced under conditions of stress that could also lead to cell death, there is growing evidence proposed on the idea that autophagy can act as a cell death mechanism . Luo et al found that the autophagy pathway is involved in the pathophysiologic responses after traumatic brain injury, and inhibition of this pathway may help attenuate traumatic damage and functional outcome deficits .…”
Section: Discussionmentioning
confidence: 99%
“…Many stimuli could induce autophagy, including nutrient starvation, mitochondrial toxins and oxidative stress (Sharma, Pandey, & Saluja, ). Recent research reported that excessive iodide could activate oxidative stress and decrease glutathione (GSH) and SOD levels, leading to increase the degree of autophagy by raising the autophagy‐related mRNA and protein expression of LC3 and beclin‐1 (Cao et al, ; Liu et al, ). Nutrient deficiency at birth can generate oxidative responses in the ovaries causing increased apoptosis and autophagy in both the somatic cells and oocyte (Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%